Effects of international R&D alliances on performance of high‐tech start‐ups: a longitudinal analysis - Colombo, Massimo G.; Grilli, Luca; Murtinu, Samuele; Piscitello, Lucia; Piva, Evila (Strategic Entrepreneurship Journal, 2009)
Abstract In this article, we use the theoretical lens of resource and competence‐based perspectives and global strategic network theory to analyze the effects of international R&D alliances on the performance of high‐tech start‐ups. In the empirical section of the article, we consider the European Union‐funded international R&D alliances established by a large sample of Italian high‐tech start‐ups over the period from 1994 to 2003. We measure firm performance through total factor productivity, and we resort to generalized method of moments system estimates to detect the treatment effect of alliance formation according to type and home country of the partners. The econometric results suggest that international R&D alliances are most beneficial to high‐tech start‐ups if (1) they involve industrial partners located in a variety of countries and (2) these countries are closer to world knowledge sources. Copyright © 2009 Strategic Management Society.